Black college students' sense of belonging and racial identity. Issue 9 (2nd September 2019) - Hunter, Carla D.; Case, Andrew D.; Harvey, I. Shevon
ABSTRACT: Black racial identity model and theory refinement has occurred in the absence of considerations of how Black college students experience and articulate their sense of belonging to the racial group. To fill this gap, the present study utilised storytelling as a framework and investigated how sense of belonging with racial in-group members was expressed in Black college students' racial identities. Qualitative phenomenological and consensual analytic approaches were employed to examine 13 (7 women, 6 men) Black freshman and sophomore undergraduate students' narratives related to sense of belonging to the racial group. The findings highlighted at least three ways in which Black college students experience and negotiate a sense of belonging to the racial group: (a) authenticating Blackness, (b) acculturative loss, and (c) connection with and responsibility toward others. Implications for racial identity research and theory are discussed.